The Effect of Arbuscular Mycorrhiza-Enriched Biocompost and Organic Fertilizer in Reducing Heavy Metal Absorption in Shallots - Akib, Muhammad Akhsan; Antonius, Sarjiya; Kuswinanti, Tutik; Syatrawati, Syatrawati; Dewi, Tirta Kumala; Sutisna, Entis (PLANTA TROPIKA, 2025)
Shallots have physiological and pharmacological effects on the human body and have been cultivated intensively using biocompost, which may be contaminated with heavy metals. Enrichment of arbuscular mycorrhizal (AM) fungi in biocompost and the addition of biological organic fertilizer (BOF) to reduce the absorption of heavy metals in shallot bulbs is the main objective of this research. The study used a Randomized Block Design with five treatments, namely: shallots cultivation method by indigenous farmers/control(B0); Dose of biocompost enriched with AM fungi 100kg plot-1(B1); 200kg plot-1(B2); 100kg plot-1+BOF(B3); 200kg plot-1+BOF(B4), has been carried out in Enrekang district, South Sulawesi by observing the components of heavy metal content in plant organs and the level of infection of AM fungi in plant roots. Results showed that a dose of biocompost enriched with AM fungi 200 kg plot-1, and 100kg plot-1+BOF could increase Cr, Cu, and Pb accumulation in roots and leaf, as well as reduce metal accumulation in shallot bulbs, with level AM fungi infection classified as very high. The novelty of this study is that organic fertilizer enriched with AM fungi can reduce the absorption of heavy metals that accumulate in shallot bulbs and is essential information for farmers.